Implementasi Karakteristik Pelayan Tuhan Menurut Filipi 2:1-11 bagi Guru Sekolah Minggu GPdI Ekklesia Jember - Pacel Zacharias; Nelly Nelly; Roberth Ruland Marini (Institut Agama Kristen Negeri Toraja, 2022)
Abstract: The main problem in this research is the character of Sunday school teachers in their service. This study focuses on the characteristics of God's servants according to Philippians 2:1-11 which aims to provide an understanding of the characteristics of God's servants to the teachers of the GPdI Ekklesia Jember Sunday School. With a qualitative approach applying descriptive analysis method to the text of Philippians 2:1-11, the results obtained are three characteristics of God's servants, namely unity, example and obedience, which can be implemented in life and ministry in the field of Sunday School.Â Keywords: Philippians 2; Sunday School Teachers; Servant of GodÂ Abstrak: Permasalahan utama dalam penelitian ini adalah karakter guru Sekolah Minggu dalam pelayanannya. Penelitian ini berfokus pada karakteristik pelayan Tuhan menurut Filipi 2:1-11 yang bertujuan untuk memberikan pemahaman mengenai karakteristik pelayan Tuhan kepada para guru Sekolah Minggu GPdI Ekklesia Jember. Dengan pendekatan kualitatif menerapkan metode deskriptif analisis pada teks Filipi 2:1-11 diperoleh hasil tiga karakteristik pelayan Tuhan yaitu kesatuan, keteladanan dan ketaatan, yang dapat diimplementasikan dalam kehidupan dan pelayanan di bidang Sekolah Minggu.Â Kata kunci: Filipi 2; Guru Sekolah Minggu; Pelayan Tuhan